2022
DOI: 10.1093/function/zqac027
|View full text |Cite|
|
Sign up to set email alerts
|

Muscle-Specific Cellular and Molecular Adaptations to Late-Life Voluntary Concurrent Exercise

Abstract: Murine exercise models can provide information on factors that influence muscle adaptability with aging, but few translatable solutions exist. Progressive weighted wheel running (PoWeR) is a simple, voluntary, low-cost, high-volume endurance/resistance exercise approach for training young mice. In the current investigation, aged mice (22-month-old) underwent a modified version of PoWeR for 8 weeks. Muscle functional, cellular, biochemical, transcriptional, and myonuclear DNA methylation analyses provide an enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(55 citation statements)
references
References 98 publications
5
48
2
Order By: Relevance
“…p=0.013) (Figure 4E), similar to what occurred in myonuclei during overload (Table S10). Type 2a myosin is associated with oxidative metabolism in murine muscle (79,80). Lower Myh2 may be part of a Warburg-like program that accompanies rapid muscle growth (38,39).…”
Section: Experiments 5: the Myc-controlled Transcriptome In Plantaris...mentioning
confidence: 99%
See 1 more Smart Citation
“…p=0.013) (Figure 4E), similar to what occurred in myonuclei during overload (Table S10). Type 2a myosin is associated with oxidative metabolism in murine muscle (79,80). Lower Myh2 may be part of a Warburg-like program that accompanies rapid muscle growth (38,39).…”
Section: Experiments 5: the Myc-controlled Transcriptome In Plantaris...mentioning
confidence: 99%
“…Library preparation for Experiment 4 was low-input and utilized the SMARTer pico kit (TaKaRa, Shiga, Japan), as described by the National Genomics Infrastructure at SciLifeLab (Stockholm, Sweden). RNA for Experiments 1, 2, 3, and 5 were sequenced by Novogene on an Illumina HiSeq using 150 bp paired-end sequencing, as we have done previously (80,104). Experiment 4 was sequenced by the SciLifeLab on a NovaSeq 6000 (150 bp paired-end).…”
Section: Rna Isolation and Sequencingmentioning
confidence: 99%
“…Upon mouse ES cell differentiation, the absence of SAMD1 enhances the expression of genes involved in neuronal pathways, while factors important for metabolism and angiogenesis are downregulated (Supplementary Figure S3) 4 . In addition to gene regulatory functions SAMD1 may also have a role in atherosclerosis 1,3 and muscle adaptation 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Further work demonstrated that SAMD1 deletion in HepG2 hepatocellular carcinoma cells leads to a global readjustment of the active H3K4me2 chromatin mark and a more favorable gene signature, supporting an oncogenic role in this context 12 . SAMD1 has also been described to play a role in antiphospholipid syndrome 14 and muscle adaptation 15 , implying a rather versatile biological function. Taken together, these ndings suggest that SAMD1 likely has a function in multiple biological processes and diseases, but the biological role of SAMD1 at an organismal level has yet to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, both acute exercise and chronic training have been shown to decrease methylation (i.e., hypomethylation) in both human and mouse skeletal muscle 17,18,35–37 . Therefore, exercise and increased physical activity are proposed to be epigenetically anti‐aging in skeletal muscle 28,29,38–42 . However, the role of exercise training on the ability to restore the epigenetic landscape and reduce the acceleration of epigenetic aging in skeletal muscle after cancer survival is currently unknown.…”
Section: Introductionmentioning
confidence: 99%